Effect of adjacent structures on footing settlement for different multi-building arrangements - Chandrawanshi Shrish; Garg Vivek (Open Engineering)
Rapid urbanization and land scarcity lead to the construction of multiple structures in proximity, supported on common soil media. This proximity increases soil stress, influencing the deformation characteristics of nearby footings. Hence, there is a need to investigate the effect of structure–soil–structure interaction (SSSI) on the footing settlement. In the present study, the effect of SSSI on the footing settlement of a three-storey building is investigated due to the presence of similar adjacent buildings arranged in various patterns (single adjacent building, side-by-side, L-shape, and inverted T-shape). The various interaction analyses are performed using finite element software ANSYS under gravity loading. The vertical and differential settlement of footings obtained from soil–structure interaction (SSI) and SSSI analyses are compared to evaluate the effect of SSSI under various adjacent building arrangements. The results indicate that in SSI case, inner footings show greater settlement compared to peripheral footings which causes high value of differential settlement between peripheral footings and those immediately adjacent to them. However, the presence of an adjacent structure in SSSI cases provides higher settlement in adjacent footings, which in turn reduces the differential settlement in these footings. Moreover, the SSSI effect on vertical settlement in SSSI (L-shaped) and SSSI (inverted T-shaped) is found to be more in corner footing located near to the adjacent buildings due to overlapping of soil stresses from two sides. The study quantifies the extent of settlement increase in various SSSI cases compared to SSI case, contributing valuable insights to mitigating potential settlement issues in densely developed areas.